Reguła Eugipiusza o funkcji opata - Czyżewski, Bogdan Stanisław (Vox Patrum, 2023)
The Regula written for the monastery in Lucullanum by Eugippius (6th c.), although not very original, has some elements that are worth paying attention to. Its author compiled eight rules of the ancient Church, most of which he had drawn from the monastic writings of St. Augustine and the Regula Magistri. In several places he shortened the sources he cited, bearing in mind the specificity of the monastery of which he was the abbot. Noteworthy are the texts about the abbot, to whom Eugippius gave, right after Christ, the highest dignity in the community. He also focused on the responsibility of the abbot for his brethren, both in the formation of their spiritual lives and in the discipline to which they were subjected in order to reach perfection. The originality of Eugippius’ Regula also lies in his “correction” of some texts he “appropriated.” Sometimes this procedure created a certain difficulty, especially with regard to his terminology referring to the abbot. He is not always consistent in using the terms abbas, praepositus and decanus, which means that we are not always able to determine exactly whom Eugippius meant. However, this does not change the fact that the abbot of the monastery in Lucullanum, thanks to the provisions contained in the Regula, was aware of his great responsibility before God and the community he headed.